Intellectual capital and technological innovation : knowledge-based theory and practice - Lopez Saez, Pedro (Hershey, PA : Information Science Reference, 2010)
'This book provides theoretical frameworks and empirical research findings to assist managers, academics and consultants gain a thorough understanding of intellectual capital and social capital as a base for improving their tasks'--Provided by publisher.
Includes bibliographical references (p. 318-360) and index.
Keywords: Intellectual capital; Technological innovations -- Social aspects